Thermal simulation of a flat-plate solar collector based on heat transfer coefficients - García López, Ángel Alfonso; García-Montalvo, Iván Antonio; Sandoval Torres, Sadoth; Pérez-Santiago, Alma Dolores; Sánchez-Medina, Marco Antonio; Matías-Pérez, Diana; Hernández-Bautista, Emilio (Frontiers in Thermal Engineering, 2026)
Renewable energy plays a crucial role in mitigating environmental impact and reducing dependence on fossil fuels. Solar thermal energy offers a clean and sustainable alternative. This study presents a phenomenological mathematical model for simulating heat transfer in a flat-plate solar collector. The model aims to optimize thermal efficiency and support the design of energy systems. The thermal analysis considers temperature gradients across the glass cover (GC), the air gap between the GC and the absorber plate (GC-AP), the aluminum absorber plate (AP), the airflow inside the tubes, and the wood insulation (WI) at the base. A thermal resistance network is developed that incorporates conduction, convection, and radiation mechanisms. Heat transfer coefficients are obtained from experimental measurements of temperature and air velocity, including ambient, GC, AP, insulation, and working fluid temperatures. These coefficients feed an energy balance model, producing differential equations that are solved numerically using Scilab Xcos to simulate the collector’s behavior. The GC acts as a selective filter, transmitting short-wave radiation and limiting long-wave emissions, contributing to a greenhouse effect that enhances performance. However, significant thermal losses occur through insulation and optical elements. Model validation against experimental data yields RMSE of 0.19 °C for natural convection and 0.0089 °C for forced convection. The thermal efficiency of 52.7% under forced convection and 29.3% under natural convection. Total energy losses amount to 35% via insulation and 15% due to optical inefficiencies. The results highlight the critical role of airflow and the importance of improving optical properties and insulation to enhance collector performance.